Peran Komunikasi dan Kerjasama Tim Dalam Kepemimpinan Pendidikan Yang Efektif - Nilda Julkiatul Rahmah; Ria Faulina; Wiwi Agustini (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Effective educational leadership requires good communication and teamwork skills. Effective communication and solid teamwork can help improve the quality of education and achieve educational goals. This article aims to discuss the role of communication and teamwork in effective educational leadership. The research method used is a systematic literature study. From the literature study, it was found that; First, there are six characteristics of effective leader communication, namely; gentle attitude, not rude in speech, not hard-hearted, forgiving and asking for forgiveness, inviting deliberation, and committing to implementing joint decisions and trusting in God. Second, effective leader communication plays a role in; 1) increasing effectiveness in sharing vision and mission; 2) improving the performance of staff, especially teachers; 3) building  partnerships  with  the  school community; 4) building a conducive school climate; 5) improving student achievement. The results of the study show that effective communication and solid teamwork can help improve the quality of education and achieve educational goals.